2015
DOI: 10.7863/ultra.34.2.333
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Infraclavicular and Supraclavicular Perineural Catheters for Ultrasound‐Guided Through‐the‐Catheter Bolus Anesthesia

Abstract: Both supraclavicular and infraclavicular perineural catheters using a through-the-catheter bolus technique provide effective brachial plexus anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…1,2) In conventional catheter therapies using X-rays, 3,4) a metal guide wire of at least 400 µm diameter is used. Because of the need of a thin catheter of 200-300 µm diameter, [5][6][7][8] we have experimented on the bending of a thin catheter with an acoustic radiation force, 9,10) which is generated when an acoustic energy density gap occurs along the ultrasound propagation direction. [11][12][13][14] The production of an acoustic radiation force was carried out through studies to control microbubbles, [15][16][17][18][19] nanobubbles, 20) and cells 21,22) using an artificial blood vessel for future use in drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) In conventional catheter therapies using X-rays, 3,4) a metal guide wire of at least 400 µm diameter is used. Because of the need of a thin catheter of 200-300 µm diameter, [5][6][7][8] we have experimented on the bending of a thin catheter with an acoustic radiation force, 9,10) which is generated when an acoustic energy density gap occurs along the ultrasound propagation direction. [11][12][13][14] The production of an acoustic radiation force was carried out through studies to control microbubbles, [15][16][17][18][19] nanobubbles, 20) and cells 21,22) using an artificial blood vessel for future use in drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…Marianao, et al in a randomized controlled trial, concluded that infraclavicular brachial plexus catheters provided superior analgesia when compared to supraclavicular brachial plexus catheters [28]. However, in another randomized control trial, no significant differences in sensory blockade, pain scores or satisfaction was reported between the two techniques [27]. In our case series, the decision was influenced in certain instances by accessibility (for example presence of a cervical collar limiting supraclavicular fossa access) and body habitus (for example a high body mass index making infraclavicular needle tip visualization more difficult).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, it has been thought that the supraclavicular approach may offer some advantages in the quality of pain control, due to the more compact arrangement of the brachial plexus [27]. Infraclavicular approach is considered more appropriate for placing a perineural catheter, because local musculature provides a more firm hold on the catheter [2,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The complications included paresthesia, injection pain related to the procedure, phrenic nerve palsy, and once more Horner syndrome ( 58 ). One randomized trial additionally found patients who received SC blocks reported higher incidence of postoperative sleep disturbances relative to those who received the IC approach ( 59 ). Other RCTs have also illustrated a lower incidence of required supplemental anesthesia or subsequent block administration – thus reducing the incidence of procedural-related pain or paresthesia and reducing the number of required needle passes ( 57 , 60 , 61 ).…”
Section: Comparison Of Safety and Efficacy Of Supraclavicular Vs Infraclavicular Approachesmentioning
confidence: 99%
“…In this study, 88% of SC patients and 100% of IC patients achieved sensory block within 30 minutes with no significant differences in the time to complete the procedure. It was thus determined that both approaches provided an optimal block with no true significant differences between the approaches ( 59 ). In the second trial, 150 patients split into two groups (SC vs. IC) were given ropivacaine ultrasound-guided blocks, and the mean procedural time, sensory block achieved, and failure rate were similar.…”
Section: Comparison Of Safety and Efficacy Of Supraclavicular Vs Infraclavicular Approachesmentioning
confidence: 99%